The immunopathogenesis of Crohn’s disease: a three-stage model - Sewell, Gavin W (Curr Opin Immunol, 2009)
The pathogenesis of Crohn’s disease (CD) has remained an enigma for at least a century. There was considerable optimism that genetic linkage and genome-wide association (GWA) studies had identified genes causally responsible. However, the realisation that these genes make a relatively minor contribution to the development of CD has led to the acceptance of a ‘missing heritability’. In contrast to the weak genetic effects, patients with CD almost without exception exhibit a gross phenotype, namely a profound systemic failure of the acute inflammatory response. This results in markedly delayed clearance of bacteria from the tissues, leading to local chronic granulomatous inflammation and compensatory adaptive immunological changes, as well as constitutional symptoms.